Preparing for the Twenty-First Century - Kennedy, Paul (Rawalpindi Services Book Club, 1995)
Looks at the different ways in which "society" prepares itself for the arrival of the 21st century. Digesting and synthesizing developments in population growth, environmental change, biotechnology, robotics and global financial markets, this book looks at a possible future
Include Table, Charts, Appendix, Notes, Bibliography and Index.
Analyzes the transnational forces that will transform nation-states in the future--population growth, environmental degradation, technological advance--their impact, and how to cope with the challenges of the future.
Keywords: Twenty-first century -- Population -- Technology--Social aspects -- History, Modern -- Social change -- World politics -- International relations -- Economic forecasting